Досвід лікування вертеброневрологічних хворих в умовах неврологічного відділення вузлової лікарні - Луцький, І.С.; Євтушенко, М.І.; Журавльова, В.П.; Туз, Ю.О.; Чаплик, О.А. (Актуальні проблеми транспортної медицини, 2006)
Обобщен опыт лечения больных вертеброневрологической патологией в условиях неврологического отделения узловой больницы. Разработан алгоритм реабилитационных мероприятий, включающий этап борьбы с болью, ликвидацию блока позвоночного двигательного сегмента, формирование мышечного корсета, восстановление привычного двигательного стереотипа. The experience of the treatment of the patients with neurovertebrological pathology under the conditions of neurological department of central hospital is generalized. They have developed the rehabilitative algorithm including pain arresting, liquidation of locomotory segment backbone block, formation of muscular corset, restoration of a habitual locomotory stereotype.